Volume 1: Large Bore Engines; Fuels; Advanced Combustion 2015
DOI: 10.1115/icef2015-1077
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Modeling and Validation of Dual-Fuel Combustion in a Large Bore Medium Speed Diesel Engine

Abstract: High fidelity, three-dimensional CFD was used to model the flow, fuel injection, combustion, and emissions in a large bore medium speed diesel engine with different levels of natural gas substitution. Detailed chemical kinetics was used to model the complex combustion behavior of the premixed natural gas, ignited via a diesel spray. The numerical predictions were compared against measured multiple cycle pressure data, to understand the possible factors affecting cyclic variation in experimental data. Under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In [107] the authors used a combination of coherent flame and surface wrinkling model and declared that in spite of capturing some physical trends, further improvements of the mixing controlled combustion are still needed. Research work was carried out with a special focus on the extended chemistry involved due to the two fuels in [108][109][110]. Eder et al showed results with an ECFM-3Z model and empiric correlations for ignition delay and laminar flame speed [111] that reasonably correlated with test data.…”
Section: Flame Propagationmentioning
confidence: 99%
“…In [107] the authors used a combination of coherent flame and surface wrinkling model and declared that in spite of capturing some physical trends, further improvements of the mixing controlled combustion are still needed. Research work was carried out with a special focus on the extended chemistry involved due to the two fuels in [108][109][110]. Eder et al showed results with an ECFM-3Z model and empiric correlations for ignition delay and laminar flame speed [111] that reasonably correlated with test data.…”
Section: Flame Propagationmentioning
confidence: 99%
“…The flame front thickness in a lean natural gas-air mixture under enginelike conditions is usually in the range of a few hundred micrometers [13], which raises the need for computational cells with a size one order of magnitude below the size that is usually used to resolve the combustion chamber to ensure an appropriate resolution of the flame front. To overcome the resulting overwhelming computational effort, some authors applied an adaptive mesh refinement to increase the local resolution in the vicinity of the flame front to generate reasonable results within certain limits [14][15][16][17][18]. However, the predicted burn rates are very sensitive to the selection of the reaction mechanism and sometimes need some additional adaption of single reaction rates [17].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the resulting overwhelming computational effort, some authors applied an adaptive mesh refinement to increase the local resolution in the vicinity of the flame front to generate reasonable results within certain limits [14][15][16][17][18]. However, the predicted burn rates are very sensitive to the selection of the reaction mechanism and sometimes need some additional adaption of single reaction rates [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a RANS simulation would not realize to a DNS simulation with sufficient grid resolution. It has been shown previously that grid resolutions in the order of 0.25 mm is sufficient to model turbulent combustion in diesel engines [11], gasoline engines [12], gasoline and diesel dual-fuel engines [13], and in natural gas and diesel dual-fuel engines [14]. Using 20 consecutive cycles, Scarcelli and Sevik [12] showed how RANS simulations can be effectively used to represent cyclic variability for EGR dilute and non-dilute gasoline engines.…”
Section: Numerical Modelmentioning
confidence: 99%
“…A recent study [14] showed 45-65% speedup using METIS for a GDI simulation using the same numerical tool. …”
Section: Numerical Modelmentioning
confidence: 99%